2016
DOI: 10.1021/acsami.6b01747
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion on Surface-Functionalized Magnesium

Abstract: The biocompatibility of commercially pure magnesium-based (cp Mg) biodegradable implants is compromised of strong hydrogen evolution and surface alkalization due to high initial corrosion rates of cp Mg in the physiological environment. To mitigate this problem, the addition of corrosion-retarding alloying elements or coating of implant surfaces has been suggested. In the following work, we explored the effect of organic coatings on long-term cell growth. cp Mg was coated with aminopropyltriehtoxysilane + vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Our findings are supported by data from Wagener et al [51] who demonstrated that MG63 osteosarcoma cells showed lower cell numbers and inhibited cell spreading when seeded directly on pure magnesium or on differently coated Mg. It was reported that the local rise in Mg level does not seem to have a significant impact on osteosarcoma cell proliferation [31,51]. High Mg levels can, however, inhibit deposition of Ca phosphate mineral matrix [52].…”
Section: Biological Propertiessupporting
confidence: 91%
“…Our findings are supported by data from Wagener et al [51] who demonstrated that MG63 osteosarcoma cells showed lower cell numbers and inhibited cell spreading when seeded directly on pure magnesium or on differently coated Mg. It was reported that the local rise in Mg level does not seem to have a significant impact on osteosarcoma cell proliferation [31,51]. High Mg levels can, however, inhibit deposition of Ca phosphate mineral matrix [52].…”
Section: Biological Propertiessupporting
confidence: 91%
“…Degradation of Mg in contact with human physiological solution involves hydrogen decomposition and an elevated pH at the implant surface. Both factors can strongly affect initial osteoblast adhesion and delay cell spreading and proliferation [47]. In this study, the TM-1 coating was less affected by the SBF corrosive attack, probably leading to lesser hydrogen decomposition.…”
Section: In Vitro Biological Propertiesmentioning
confidence: 63%
“…It was expected that the coatings containing Mg would show lower cell numbers than of uncoated Ti6Al4V. It has already been demonstrated that cell adhesion and proliferation of MG63 osteosarcoma cells is inhibited in direct contact with pure Mg surfaces or Mg-based coatings [47,48]. A possible explanation for this could be due to the Mg ions being released from the surface of the implant.…”
Section: In Vitro Biological Propertiesmentioning
confidence: 99%
“…Cell adhesion is unlikely to occur directly on the implant. Thus, an appropriate surface treatment is needed [5]. For this treatment, several biomimetic coatings are investigated: Aminopropyltriehtoxysilane, vitamin C (AV), carbonyldiimidazole (CDI), stearic acid (SA), aminated hydroxyethyl cellulose, gelatin, and peptides [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%